Molding of Polymeric Composite Reinforced with Glass Fiber and Ceramic Inserts: Mathematical Modeling and Simulation - Túlio R. N. Porto; Wanderley F. A. Júnior; Antonio G. B. De Lima; Wanderson M. P. B. De Lima; Hallyson G. G. M. Lima (Advances in Materials Science and Engineering)
This work provides a numerical study of a polymer composite manufacturing by using liquid composite material molding. Simulation of resin flow into a porous media comprising fiber perform (reinforcement) inserted in a mold with preallocated ceramic inserts has been performed, using the Ansys FLUENT® software. Results of resin volumetric fraction, stream lines and pressure distribution inside the mold, and mass flow rate (inlet and outlet gates) of the resin, as a function of filling time, have been presented and discussed. Results show that the number of inserts affects the filling time whereas the distance between them has no influence in a process.